Comparative Analysis of Closed Versus Open Interlocking Intramedullary Nailing for Femoral Shaft Fractures - Malik Muhammad Abbas; Usman Habib; Farasat Umar; Babar Shahzad Sadiq; Saleem Ahmed Bhutto; Syed Irfan Raza Arif (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Femoral shaft fractures are commonly caused by high-energy trauma and are often managed through intramedullary nailing. Both closed and open interlocking nailing techniques are employed, but their outcomes remain debated. This study compares the clinical and radiological outcomes of closed versus open interlocking nailing for femoral shaft fractures. Methods: This prospective comparative study included 106 patients with femoral shaft fractures treated with interlocking intramedullary nailing. The cohort was divided into two groups: closed reduction (Group A) and open reduction (Group B). Outcomes assessed included union time, complication rates, functional recovery, and patient satisfaction. Results: Union time was shorter in Group A compared to Group B (p < 0.05). The complication rate was significantly lower in the closed reduction group (p < 0.05). Functional outcomes, as assessed by the Harris Hip Score, were superior in Group A. Conclusion: Closed interlocking nailing is associated with better outcomes in terms of shorter union time, fewer complications, and better functional recovery compared to open interlocking nailing.